2021
DOI: 10.1038/s41598-021-85812-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct DNA methylation patterns associated with treatment resistance in metastatic castration resistant prostate cancer

Abstract: Androgens are a major driver of prostate cancer (PCa) and continue to be a critical treatment target for advanced disease, which includes castration therapy and antiandrogens. However, resistance to these therapies leading to metastatic castration-resistant prostate cancer (mCRPC), and the emergence of treatment-induced neuroendocrine disease (tNEPC) remains an ongoing challenge. Instability of the DNA methylome is well established as a major hallmark of PCa development and progression. Therefore, investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…On the contrary, AZA profoundly modified DNA methylation pattern, sustaining a pervasive hypomethylation of the genome. Pathways analysis on the list of DMPs identified several biological processes associated with NED in previous studies [2, 11, 27] such as neural functions and axonal guidance but also others involved in regulation of cell migration, proliferation, and apoptosis. In particular, the most enriched pathway was Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the contrary, AZA profoundly modified DNA methylation pattern, sustaining a pervasive hypomethylation of the genome. Pathways analysis on the list of DMPs identified several biological processes associated with NED in previous studies [2, 11, 27] such as neural functions and axonal guidance but also others involved in regulation of cell migration, proliferation, and apoptosis. In particular, the most enriched pathway was Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 97%
“…The authors suggested that this DNA methylation remodeling was associated to transition to neuroendocrine PC subtype [2]. Accordingly, using a xenograft model of CRPC, Peter et al [27] demonstrated that DNA methylation progressively changes from the castration naïve state to the treatment-induced NED state. These epigenetic alterations were likely able to affect gene expression of genes related to neurodevelopmental and morphogenic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation profiling of cfDNA is also showing promise in understanding epigenomic patterns in tumor cells contributing to ctDNA, and has promise for clinical detection of neuroendocrine prostate cancer. 111,112 Furthermore, exciting new data suggest that it will be possible to detect active histone modifications in cells contributing to ctDNA through chromatin immunoprecipitation of cell-free nucleosomes (cfChIP-seq), direct from patient plasma. 113 Advances in single-cell profiling technology are now also improving resolution of genomic alterations in CTCs.…”
Section: Mutations In the Ar Lbdmentioning
confidence: 99%
“…Since nucleosome occupancy can be inferred using cfDNA whole genome sequencing, it is plausible that cfDNA profiling may eventually help predict AR activity in prostate cancer cells, and therefore better define the relevance of detecting synchronous AR genomic alterations. Methylation profiling of cfDNA is also showing promise in understanding epigenomic patterns in tumor cells contributing to ctDNA, and has promise for clinical detection of neuroendocrine prostate cancer 111,112 . Furthermore, exciting new data suggest that it will be possible to detect active histone modifications in cells contributing to ctDNA through chromatin immunoprecipitation of cell‐free nucleosomes (cfChIP‐seq), direct from patient plasma 113 .…”
Section: Future Directionsmentioning
confidence: 99%